Aryl Bis‐Sulfonamide Inhibitors of IspF from Arabidopsis thaliana and Plasmodium falciparum. Issue 12 (5th October 2015) - Thelemann, Jonas; Illarionov, Boris; Barylyuk, Konstantin; Geist, Julie; Kirchmair, Johannes; Schneider, Petra; Anthore, Lucile; Root, Katharina; Trapp, Nils; Bacher, Adelbert; Witschel, Matthias; Zenobi, Renato; et al.
Abstract: 2‐Methylerythritol 2, 4‐cyclodiphosphate synthase (IspF) is an essential enzyme for the biosynthesis of isoprenoid precursors in plants and many human pathogens. The protein is an attractive target for the development of anti‐infectives and herbicides. Using a photometric assay, a screen of 40 000 compounds on IspF from Arabidopsis thaliana afforded symmetrical aryl bis‐sulfonamides that inhibit IspF from A. thaliana ( At IspF) and Plasmodium falciparum ( Pf IspF) with IC50 values in the micromolar range. The ortho ‐bis‐sulfonamide structural motif is essential for inhibitory activity. The best derivatives obtained by parallel synthesis showed IC50 values of 1.4 μm against Pf IspF and 240 nm against At IspF. Substantial herbicidal activity was observed at a dose of 2 kg ha −1 . Molecular modeling studies served as the basis for an in silico search targeted at the discovery of novel, non‐symmetrical sulfonamide IspF inhibitors. The designed compounds were found to exhibit inhibitory activities in the double‐digit micromolar IC50 range. Abstract : High‐throughput screening identified a symmetrical aryl bis‐sulfonamide inhibitor of the enzyme IspF from the non‐mevalonate pathway for isoprenoid biosynthesis. Further derivatization afforded active ligands with IC50 values of 240 nm against Arabidopsis thaliana IspF and 1.4 μm against Plasmodium falciparum IspF. Activity against IspF was measured by photometric, HPLC, ITC, and ESI‐MS methods. A binding mode in accordance with the structure–activity relationship was proposed based on docking studies.